2020
DOI: 10.1155/2020/1682904
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sodium-Glucose Cotransporter 2 Inhibition on Glucose Metabolism, Liver Function, Ascites, and Hemodynamics in a Mouse Model of Nonalcoholic Steatohepatitis and Type 2 Diabetes

Abstract: Many blood glucose-lowering drugs cannot be used once patients with type 2 diabetes (T2D) and nonalcoholic fatty liver disease develop nonalcoholic steatohepatitis (NASH). Therefore, such patients often require insulin treatment. We aimed to determine the effect of sodium-glucose cotransporter 2 inhibitor (SGLT2i) dapagliflozin monotherapy on glucose metabolism in a mouse model of NASH/T2D, with a focus on its diuretic effects. To imitate ascites and to determine its severity by imaging, meglumine sodium amido… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
1
5
0
1
Order By: Relevance
“…To further explore whether OVGP1-induced hypertension is mediated through pathologic alteration of vascular function, we used different antihypertensive drugs to reduce BP in transgenic and nontransgenic mice 26,27 ; the diuretic furosemide did not ameliorate the difference between transgenic and nontransgenic mice, whereas the vasodilator prazosin did (Figure S9). These results indicated that the effect of OVGP1 overexpression on BP is mediated by pathologic alteration of the blood vessels.…”
Section: Resultsmentioning
confidence: 99%
“…To further explore whether OVGP1-induced hypertension is mediated through pathologic alteration of vascular function, we used different antihypertensive drugs to reduce BP in transgenic and nontransgenic mice 26,27 ; the diuretic furosemide did not ameliorate the difference between transgenic and nontransgenic mice, whereas the vasodilator prazosin did (Figure S9). These results indicated that the effect of OVGP1 overexpression on BP is mediated by pathologic alteration of the blood vessels.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were observed in HFD-fed C57BL/6J male mice after administration of canagliflozin ( Table 2 ) at 30 mg/kg dose for four weeks in parallel with improvement of liver function, liver TG content and NAS score [ 108 ]. Additionally, short term and low dose administration of dapagliflozin ( Table 3 ) reduced both ALT levels and body weight in both HFD and HFD+MCD diet fed C57BL/6J mice [ 109 ]. However, it should be noted that not all studies point towards a beneficial effect of SGLT-2i on body weight.…”
Section: Sglt-2 Inhibitors In Nafldmentioning
confidence: 99%
“…However, the protective role of SGLT-2i against NAFLD progression also seems to be mediated by effects beyond those on body weight. Indeed, it has been shown that SGLT-2i treatment improves IR and ameliorates the intracellular FFA, total cholesterol (TC) and TG accumulation through reducing the expression of genes involved in de novo lipogenesis, FA uptake and hepatic TG secretion, whilst it also promotes the expression of key regulatory genes of fatty acid β-oxidation [ 30 , 84 , 100 , 107 , 109 , 112 , 117 ]. Specifically, empagliflozin administration has been shown to reduce hepatic triacylglycerol (TAG) levels and improve IR through reduction of lipotoxic intermediates formation, such as diacylglycerols (DAG) [ 115 ], which at elevated levels contribute to IR by activating the protein kinase C (PKC)ε pathway [ 118 ].…”
Section: Sglt-2 Inhibitors In Nafldmentioning
confidence: 99%
“…С целью имитации асцита в брюшную полость мышей вводили амидотризоат натрия меглюмина (MSA), было проведено сравнение регрессии асцита, индуцированной приемом дапаглифлозина, с таковой на фоне приема фуросемида с использованием микрокомпьютерной томографии. В ходе эксперимента было показано, что дапаглифлозин обладал более эффективным диуретическим эффектом без отрицательного влияния на гемодинамику, что предполагает возможное применение в терапии цирроза печени [47].…”
Section: механизмы гепатопротекторного действия ингибиторов натрий-гл...unclassified